2018
DOI: 10.3892/etm.2018.6596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential of chicoric acid as a natural food antioxidant

Abstract: Dietary fat is important for human health, while its excessive consumption or the oxidation of lipids may cause various diseases. In the present study, the potential of chicoric acid (CA) as a natural food antioxidant was evaluated. To evaluate this, spectrophotometry analysis measured CA antioxidant activity, the analytical method of the sanitary standard of edible lard and rapeseed oil measured CA anti-oil oxidation, the Oxford cup method measured CA anti-microbial activity, Oil red O staining assessed intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The major active compounds in PCE are caftaric acid, polydatin, rutin, quercitrin, and resveratrol. The five active compounds are present in many natural plant extracts, and previous studies have demonstrated that they have anti-inflammatory and anti-oxidative properties [ 48 , 49 , 50 ]. Therefore, PCE may promote anti-oxidative activity in DED by recovering expression of anti-oxidant proteins such as HO-1, SOD-1, and GPx in hyperosmolar stressed HCECs.…”
Section: Discussionmentioning
confidence: 99%
“…The major active compounds in PCE are caftaric acid, polydatin, rutin, quercitrin, and resveratrol. The five active compounds are present in many natural plant extracts, and previous studies have demonstrated that they have anti-inflammatory and anti-oxidative properties [ 48 , 49 , 50 ]. Therefore, PCE may promote anti-oxidative activity in DED by recovering expression of anti-oxidant proteins such as HO-1, SOD-1, and GPx in hyperosmolar stressed HCECs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chicoric acid possesses various functional properties including antioxidant, antivirus and immunoregulation. [28,29] Particularly, chicoric acid is a potent inhibitor of the integrase of the Type 1 human immunodeficiency virus (HIV-1). [30] Additionally, Lee and Scagel [28] indicated that chicoric acid helps a plant protect itself from insects and infection from viruses, bacteria, fungi, and nematodes and that it aids in wound healing in plants after mechanical damage.…”
Section: Rp-hplc Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…Moreover, C. intybus leaves are specifically rich in chicoric acid as reported [ 63 , 67 ]. Chicoric acid, a caffeic acid derivative, has been also regarded as a nutraceutical with antioxidant and anti-inflammatory activities [ 68 , 69 ] as well as antioxidant effects, important for human health [ 70 ]. In addition to anti-inflammation [ 69 , 71 , 72 ] and antioxidation effects [ 73 , 74 ], the main benefits of chicoric acid also include antiviral [ 75 , 76 , 77 ], glucose and lipid homeostasis [ 78 , 79 ] and neuroprotection [ 80 ] activities.…”
Section: Resultsmentioning
confidence: 99%